Malay Version of the Family Satisfaction Scale: Validity and Reliability among Malaysian Working Women - Sanaz Aazami,; Khadijah Shamsuddin,; Syaqirah Akmal, (Universiti Kebangsaan Malaysia, 2015)
Introduction Family satisfaction is referred to the extent in which family members feel happy and fulfilled with each other. However, there has been lack of on the family satisfaction scale within the Malaysian context.Therefore, the aim of this study was to assess validity of the Malay version of the Olson’s Family Satisfaction Scale. This is to allow Malaysian researchers to bring family satisfaction in line with the different field of studies. Methods This study was conducted among 567 Malaysian working women. Data were collected using self-administrated questionnaires. This study conducted exploratory and confirmatory factor analysis, convergent validity and internal consistency using Cronbach’s alpha. Results The findings of this study support the uni-dimensionality of the Malay version of the family satisfaction scale. The 10 items of the scale account for 68.1% of the total variance and the un-rotated factor loadings ranged from 0.76 to 0.87. Confirmatory factor analysis was run and supported the structure of family satisfaction scale. The results of confirmatory factor analysis using AMOS 21 in the current study reported the following indices: RMSEA= 0.06, CFI= 0.94, NFI= 0.94, TLI= 0.93. The convergent validity (average variance extracted= 0.65) and the internal consistency (Cronbach’s alpha= 0.94) of this construct were adequately supported. Conclusions The findings support the factor structure, convergent validity and the internal consistency of the examined construct. Therefore, Malay version of the family satisfaction scale is a valid and reliable instrument among Malaysian working women.